Structural Analysis of a Polysaccharide Isolated from the Alkali Extract of an Edible Mushroom, Pleurotus sajor-caju, Cultivar Black Japan - Ojha, A. K. (Journal of Scientific Research, 2021)
A heteropolysaccharide (PS-I) and an insoluble glucan (PS-II) were isolated from the alkaline extract of an edible mushroom Pleurotus sajor-caju, cultivar Black Japan. The polysaccharide (PS-I) was found to consist of D-glucose and D-galactose in a molar ratio of 3:1. Based on total acid hydrolysis, methylation analysis, and NMR experiments (1H, 13C, DQF-COSY, TOCSY, NOESY, ROESY, HMQC, and HMBC), the structure of the repeating unit of the polysaccharide was established.